Narcissism and gift giving: Not every gift is for others. (July 2016) - Hyun, Na Kyong; Park, Yoobin; Park, Sun W.
Abstract: Although previous studies have suggested that narcissism and self-esteem carry different interpersonal implications, few have examined their differences in specific motivations behind relationship behaviors. This article detailed an exploratory study to identify romantic gift-giving motivations and examined their relations to the two personality constructs. Young adults in a romantic relationship completed measures of narcissism and self-esteem, and responded to questions about gift-giving motivations both in an actual past occasion and in a hypothetical future occasion. A factor analysis found three motivations for romantic gift giving: intrinsic, maintenance, and power motivation. When self-esteem, age, and sex were controlled, narcissism was positively related to maintenance motivation in the past, and maintenance and power motivation in the future. Self-esteem was negatively related to power motivation in the past and maintenance motivation in the future, controlling for narcissism, age, and sex. Our results suggest that narcissistic individuals critically differ from those with high self-esteem in their tendency to consider gift giving an instrumental act. Highlights: We examined how narcissism and self-esteem are related to gift-giving motivations. Narcissism is associated with high motivation for maintenance and power. Self-esteem is associated with low motivation for maintenance and power.